Handbook of reading disability research - McGill-Franzen, Anne.; Allington, Richard L. (New York Routledge, 2011)
"This book examines reading disabilities from sociopolitical and historical perspectives, as cultural and psychological constructs, from the point of view of an interventionist, and emphasizing that learning to read proficiently is long-term developmental process involving many interventions of various kinds, all keyed to individual developmental needs."--Cover.
The political contexts of reading disabilities / Patrick Shannon and Jacqueline Edmondson -- Second language reading disability : international themes / Lee Gunderson, Reginald D?Silva, and Louis Chen -- Reader profiles and reading disabilities / Sheila W. Valencia -- Language development and reading disabilities / Ludo Verhoeven -- Sociocultural perspectives on children with reading difficulties / Ellen McIntyre -- Instructional texts and the fluency of learning disabled readers / Shailaja Menon and Elfrieda H. Hiebert -- Teacher education and reading disabilities / Susan M. Benner, Sherry Mee Bell, and Amy D. Broemmel -- Neuroscience and dyslexia / Steven L. Strauss -- Home differences and reading difficulty / Jeanne R. Paratore and Susan Dougherty -- Persistent reading disabilities : challenging six erroneous beliefs / Linda M. Phillips, Denyse V. Hayward, and Stephen P. Norris -- Prenatal drug and alcohol exposure and reading disabilities / Diane Barone -- Aliteracy, agency, and identity / Stergious Botzakis and Leigh A. Hall -- Response to intervention as an assessment approach / Donna M. Scanlon -- Patterns of reading disabilities across development / Louise Spear-Swerling -- Traditions of diagnosis : learning from the past, moving past traditions / Kathleen A. Gormley and Peter McDermott -- Reading fluency : what is it and how should it be measured? / S.J. Alt and S. Jay Samuels -- Shifting perspectives in emergent literacy research / Renée M. Casbergue and Lea McGee -- Developmental patterns of reading proficiency and reading difficulties / Marcia Invernizzi and Latisha Hayes -- Vocabulary development and implications for reading problems / Andrew Biemiller -- Reading comprehension and reading disability / Katherine K. Frankel, P. David Pearson, and Marnie Nair -- Writing difficulties / Steve Graham and Karen Harris -- Motivation and reading disabilities / Mark J. van Ryzin -- The contribution of discussion to reading comprehension and critical thinking / Jacquelynn A. Malloy and Linda B. Gambrell -- Expert classroom instruction for students with reading disabilities : explicit, intense, targeted and flexible / Ruth Wharton-McDonald -- Cultural modeling : building on cultural strengths as an alternative to remedial reading approaches / Marjorie Faulstich Orellana, Jennifer Reynolds, and Danny Cortez Martínez -- Interventions to develop phonological and orthographic systems / Darrell Morris -- Interventions to develop decoding proficiencies / Irene W. Gaskins -- Interventions to enhance fluency and rate of reading / Melanie R. Kuhn -- Interventions to enhance vocabulary development / Michael F. Graves and Rebecca Silverman -- Interventions to enhance narrative comprehension / Janice F. Almasi, Barbara Martin Palmer, Angie Madden, and Susan Hart -- Interventions to enhance informational text comprehension / Nicole M. Martin and Nell K. Duke -- Peer mediation : a means of differentiating classroom instruction / Douglas Fuchs, Lynn S. Fuchs, Adina Shamir, Eric Dion, Laura M. Saenz, and Kristen L. McMaster -- Reading instruction research for English-language learners in kindergarten through sixth grade : the last twenty years / Steve Amendum and Jill Fitzgerald -- Interventions for the deaf and language delayed / Kimberly A. Wolbers and Hannah M. Dostal -- Teacher research on reading difficulties / James F. Baumann and T. Lee Williams -- Single-subject and case-study design / David Cihak -- Experimental and quasi-experimental designs for interventions / Victor L. Willson and William Rupley -- Observational research / Misty Sailors and Margaret Flores -- Large database analyses / Therese D. Pigott and Kenneth Wong -- Policy, research, and reading first / Naomi Zigmond, Rita Bean, Amanda Kloo, and Melissa Brydon -- Meta-analysis of research on children with reading disabilities / H. Lee Swanson -- Interpretive research / Donna E. Alvermann and Christine A. Mallozzi.
Keywords: Reading disability -- Research -- Handbooks, manuals, etc